Training Mental Health Cadres in Improving Screening Skills for Mental Problems in School Health Unit at Junior High School 23 Padang - Bunga Permata Wenny; Mahathir; Atih Rahayu Ningsih; Windy Freska; Devia Putri Lenggogeni; Rika Sarfika; Randy Refnandes; Siti Yuliharni; Kiki Hardiansyah Safitri; Siti Mutia Kosassy; Ramaita (Warta Pengabdian Andalas, 2025)
Adolescents face various risk factors that increase vulnerability to their mental health. The purpose of this activity is to train and empower adolescent mental health cadres at SMPN 23 Padang to recognize and resolve mental health problems independently. The methods used include socialization, counseling, and workshops on the implementation of the School Mental Health Unit program with a focus on preventing mental health problems and deviant behavior. The partners of this activity were teachers and the UKS team of SMPN 23 Padang, who were selected as mental health cadres. The results showed a significant increase in skills; whereas before the training, only 41.7% of cadres were skilled in conducting mental health screening, while after the training, it reached 100%. This activity proves that involving adolescents in solving mental health problems can significantly improve their skills.